2012
DOI: 10.1007/s10910-012-0075-x
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of the empirical shifted Deng–Fan oscillator potential for diatomic molecules

Abstract: We obtain the bound-state solutions of the radial Schrödinger equation (SE) with the shifted Deng-Fan (sDF) oscillator potential in the frame of the Nikiforov-Uvarov (NU) method and employing Pekeris-type approximation to deal with the centrifugal term. The analytical expressions for the energy eigenvalues and the corresponding wave functions are obtained in closed form for arbitrary l -state. The ro-vibrational energy levels for a few diatomic molecules are also calculated. They are found to be in good agreem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 55 publications
4
72
0
Order By: Relevance
“…Very recently, Wang and co-workers found that the Manning-Rosen, Deng-Fan and Schiöberg potential are not better than the traditional Morse potential in simulating the atomic interaction for diatomic molecules [28]. In order to overcome this problem, Hamzavi et al suggested a modification to the Deng-Fan potential, which they referred to as the shifted Deng-Fan potential (sDF) [17]. This modification is simply a Deng-Fan potential [19,20] shifted by dissociation energy D [17].…”
Section: Shifted Deng-fan Molecular Potentialmentioning
confidence: 99%
See 4 more Smart Citations
“…Very recently, Wang and co-workers found that the Manning-Rosen, Deng-Fan and Schiöberg potential are not better than the traditional Morse potential in simulating the atomic interaction for diatomic molecules [28]. In order to overcome this problem, Hamzavi et al suggested a modification to the Deng-Fan potential, which they referred to as the shifted Deng-Fan potential (sDF) [17]. This modification is simply a Deng-Fan potential [19,20] shifted by dissociation energy D [17].…”
Section: Shifted Deng-fan Molecular Potentialmentioning
confidence: 99%
“…In order to overcome this problem, Hamzavi et al suggested a modification to the Deng-Fan potential, which they referred to as the shifted Deng-Fan potential (sDF) [17]. This modification is simply a Deng-Fan potential [19,20] shifted by dissociation energy D [17]. The researchers [17] examined the Schrödinger equation with this potential and applied their results to some diatomic molecules [17].…”
Section: Shifted Deng-fan Molecular Potentialmentioning
confidence: 99%
See 3 more Smart Citations